Evaluating soil quality in silvopastoral systems by the Soil Management Assessment Framework (SMAF) in the Colombian Amazon - Pablo Chavarro Bermeo, Juan (Revista Ciência Agronômica, 2021)
Monitoring the infl uence of livestock systems’ on soil quality (SQ) in the Colombian Amazon region is important to ensure the sustainability of those agroecosystems. Here we used the Soil Management Assessment Framework (SMAF) to assess the SQ responses to land-use change associated with the adoption of silvopastoral systems (SPS) at two study sites in the Colombian Amazon region. A chronosequence formed by three land-use systems, refl ecting the typical land transition performed in the region, was established at each study site: i) native vegetation (NV), ii) pasture (PAST), and iii) SPS. Soil samples were collected at 10 cm deep increments until reaching 30 cm deep. Then soil pH, potassium, available phosphorus, microbial carbon, soil organic carbon, and bulk density were measured. In addition, data from Visual Evaluation of Soil Structure (VESS) were correlated. Data were interpretated using SMAF algorithms, and a Soil Quality Index (SQI) was calculated. Our data showed an SQ degradation due to land-use change from NV to PAST, with soils reducing their capacity of soils function from 0.72 to 0.62. The establishment of SPS over extensive PAST restored soil quality (SQI = 0.69) compared to PAST (both sites), even reaching similar SQI values to those observed in NV at site 1. The SMAF showed to be a potential tool to monitor the SQ in low-fertility soils from the Colombian Amazon region. The VESS scores were also correlated with SMAF - scores, proving to be a simple and complementary tool for farmers to monitor SQ in the Amazon region.